Efektivitas Terapi Relaksasi Otot Progresif dan Senam Hipertensi dalam Menurunkan Tekanan Darah pada Lansia Penderita Hipertensi - Wulandari, Tri; Adriani, Rita Benya; Sunaryo, Tri (Bima Nursing Journal, 2024)
The biggest death in the world due to hypertension, cases of hypertension increase with age. Treatment of hypertension can be done using nonpharmacological therapies such as progressive muscle relaxation therapy and hypertension exercise which have been proven to reduce systolic and diastolic blood pressure. Knowing the difference in effectiveness between progressive muscle relaxation therapy and hypertension exercise in reducing blood pressure in hypertension sufferers in Margorejo Gilingan Village, Banjarsari, Surakarta. This type of research uses a quasi-experimental design with a pretestposttest design without a control group design. The sampling technique used purposive sampling with a sample of 60 respondents which were divided into two groups, namely 30 respondents in the progressive muscle relaxation therapy intervention group and 30 respondents in the hypertension exercise intervention group. Data analysis using Wilcoxon test and Mann Whitney test. The results of the Wilcoxon test in the progressive muscle relaxation therapy intervention group and the hypertension exercise intervention group showed a decrease in systolic and diastolic blood pressure with a Sig value. (2- tailed) in both groups, namely 0.000 where the p value. Conclusion: There is a significant difference between progressive muscle relaxation therapy and hypertension exercise in lowering blood pressure in elderly people with hypertension.